Pengaruh Zakat Profesi dan Infak terhadap Kesejahteraan Perekonomian Mustahik di Badan Amil Zakat Nasional Kabupaten Mojokerto - Muhamad Lutfi Nurhana; Diah Syifaul A'yuni; Muawanah (Prodi Ekomoni Syariah STAI Al Akbar Surabaya, 2024)
In human life, poverty and economic inequality are very significant problems that occur in Indonesia. One of the causes of recent poverty is the Covid-19 pandemic which has hit Indonesia for two years, especially in the province of East Java, where the percentage of poverty during the pandemic has increased. However, humans never stop looking for ways to transition to a prosperous life. One of them is that in Islam there are concepts for alleviating poverty and economic inequality, one of which is professional zakat and infaq. So, based on the problems above, researchers tested the influence of professional zakat and infaq on economic welfare partially and simultaneously using quantitative methods. The data used is primary data and secondary data. Data collection was carried out using questionnaires distributed to respondents. The respondents in this study were the mustahik of the Badan Nazional Amil Zakat, Mojokerto Regency with a population of thirteen thousand, eight hundred and ninety-seven and a sample of one hundred respondents was taken. The technique used in this research is the multiple linear regression test. And the results of this research show that there is a partial influence between professional zakat on economic welfare, there is a partial influence between infaq on economic welfare and simultaneously there is an influence between professional zakat and infaq on economic welfare.